Effect of crude extract and polysaccharides derived from Fucus spiralis on radish plants Raphanus sativus L. agrophysiological traits under drought stress - Safaa Er-rqaibi; Karim Lyamlouli; Houda El Yacoubi; Mohammed El Mehdi El Boukhari (BMC Plant Biology)
Abstract Drought is a significant environmental stressor that induces changes in the physiological, morphological, biochemical, and molecular traits of plants, ultimately resulting in reduced plant growth and crop productivity. Seaweed extracts are thought to be effective in mitigating the effects of drought stress on plants. In this study, we investigated the impact of crude extract (CE), and polysaccharides (PS) derived from the brown macroalgae Fucus spiralis (Heterokontophyta, Phaeophyceae) applied at 5% (v/v) and 0.1% (w/v) respectively on radish plants Raphanus sativus L. subjected to varying levels of drought stress, specifically 80% of field capacity (FC) for no stress, 60% FC for moderate stress, and 40% FC for severe stress. Our examination of growth parameters, along with physiological and biochemical characteristics, revealed that both CE and PS increased the fresh weight over the control by 47.43% and 64% at 40% FC and 12.5% and 38% at 60% FC respectively. Under stress (40% FC), the application of CE and PS decreased proline content of radish leaves by 23.45% and 6.46% respectively in comparison with the control. Furthermore, PS treatment caused an increase of the alkaline phosphatase and urease activity in the soil by 182.5% and 34.6% respectively. CE and PS treatments led to decreased sugar content and total phenolics levels. Notably, lipid peroxidation was reduced in stressed plants treated with both CE and PS, with PS treatment yielding lower concentrations (3.75 nmol MDA.g− 1 FW at 40% FC). Overall, F. spiralis extracts interacted through several mechanisms using various compounds to mitigate the negative effects of drought stress on radish plants. These results demonstrate that seaweed extracts could be adopted in integrated production systems to boost food productivity under harsh climatic conditions.